Issues of German-Russian glossary creation at translation of texts of militarytechnical theme - V. N. Belyaeva; I. R. Levin (Омский научный вестник: Серия "Общество. История. Современность")
This article is dedicated to the analysis of a translation glossary creation experience, which can become a demanded and authoritative lexicographic resource, a valuable source of ready-made solutions in text translation, when a translator’s competence is needed. Particularly this work has an applied character but it also allows us to formulate some conclusions about linguistic features of the terminology prevailing in special texts concerning air-defense systems; to study the use of Russian analogue texts in a translation practice; to describe a macro- and microstructure of a future military and technical dictionary